A temática das violências contra as mulheres na formação continuada de professoras/es: “Quando eu crescer, quero ser igual ao meu pai [...] É, eu quero fazer com minha esposa a mesma coisa que ele fez com minha mãe, matou ela” - Natividade, Mariane Avelar (2020)
This research sought to identify which are the representations of teachers in the process of continuing education about violence suffered by women. For that, as part of the discipline "School, Curriculum and Cultural Diversity" component of the Professional Master in Education at UFLA, a workshop was created and applied that, based on cultural artifacts, stimulated debates and reflections where relations of power, knowledge and truth could be analyzed and problematized. This relationships manufacture everyday and subjects, as well as violence and also the so-called rape culture, where women and their bodies are objectified and placed as if they were always at the service of men. Thus, it is interesting and necessary that we think of ways and strategies to transform this reality. In this sense, through post-structuralism theories we seek to understand statements, in addition to creating dialogues with (and in) education, since it plays an important pedagogical role on genders and sexualities. And it is in this context that we find space and opportunity to approach and develop Feminist Pedagogy, an education perspective that is guided precisely in creating dialogues, expanding relationships and making power circulate, so as to deconstruct and build new ways of being, embracing differences and expanding possibilities of existence. Therefore, it is hoped that this research has contributed to the breaking of stereotypes and discourses aimed at maintaining a hegemonic power, where the male figure occupies the place of privilege, naturalizing violence not only against women, but also against other minorities that are excluded daily by oppressive and limited standards. Finally, and consequently, beyond finding answers, we seek to create questions and problematizations in order to enable reflections and new ways of being in the world.